Budaya Mutu dan Implementasi ISO 2008: 9001 serta Dampaknya terhadap Komitmen Organisasional - Muafi, Muafi; Nilmawati, Nilmawati (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2014)
The objective of this research was to analyze the influence of quality culture toward the implementation process of ISO 9001:2008 and its impacts on organizational commitment. The researcher analyzed the lecturers and staffs perception at Management Master Program, Universitas Pembangunan Nasional Veteran Yogyakarta (MM UPNVY) on the role importance of quality culture in the implementation process of ISO 9001:2008 and its impacts on organizational commitment. This study was expected to give benefits for MM and UPN Veteran Yogyakarta in implementing ISO 2008:9001, so the best policies and decision can be taken to improve the performance of MM UPNVY. The population of thisÃ‚Â study was lecturers and staff at MM, UPNVY. The samples were taken by census. Then, the data were analyzed by Partial Least Square (PLS) statistical technique. The result showed that (1) quality culture gave positive and significant influence toward the implementation of quality management system, (2) the implementation of quality management system gave positive and significant influence toward organizational commitment.